2006
DOI: 10.1016/j.specom.2005.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Robust spoken language understanding in a computer game

Abstract: We present and evaluate a robust method for the interpretation of spoken input to a conversational computer game. The scenario of the game is that of a player interacting with embodied fairy-tale characters in a 3D world via spoken dialogue (supplemented by graphical pointing actions) to solve various problems. The player himself cannot directly perform actions in the world, but interacts with the fairy-tale characters to have them perform various tasks, and to get information about the world and the problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The DM is based on work described previously (Boye & Gustafson, 2005;Boye, Gustafson, & Wirén, 2006;Boye, 2007), but has been substantially modified for the challenges of conversational dialogue. It receives user utterances from the NLU as semantic representa-tions (right side of Figure 3).…”
Section: Dialogue Managementmentioning
confidence: 99%
“…The DM is based on work described previously (Boye & Gustafson, 2005;Boye, Gustafson, & Wirén, 2006;Boye, 2007), but has been substantially modified for the challenges of conversational dialogue. It receives user utterances from the NLU as semantic representa-tions (right side of Figure 3).…”
Section: Dialogue Managementmentioning
confidence: 99%
“…The DM is based on work described previously (Boye & Gustafson, 2005;Boye, Gustafson, & Wirén, 2006;Boye, 2007), but has been substantially modified for the challenges of conversational dialogue. It receives user utterances from the NLU as semantic representations (right side of Figure 3).…”
Section: Dialogue Managementmentioning
confidence: 99%
“…Gallwitz et al [24] also found in sentences' prosodic limits a new manner to segment and identify words. Lastly, prosody helps in dialog acts determination without independent syntactic and semantic analysis [25] and in games control contextualization [26] [27].…”
Section: Related Workmentioning
confidence: 99%